Provincial Health Accounts in Kerman, Iran: An Evidence of a "Mixed" Healthcare Financing System - Mohammad Hossein Mehrolhassani; Mohammad Jafari; Javad Zeinali; Mina Ansari (Kerman University of Medical Sciences, 2014)
Background Provincial Health Accounts (PHA) as a subset of National Health Accounts (NHA) present financial information for health sectors. It leads to a logical decision making for policy-makers in order to achieve health system goals, especially Fair Financial Contribution (FFC). This study aimed to examine Health Accounts in Kerman Province. Methods The present analytical study was carried out retrospectively between 2008 and 2011. The research population consisted of urban and rural households as well as providers and financial agents in health sectors of Kerman Province. The purposeful sampling included 16 provincial organizations. To complete data, the report on Kerman household expenditure was taken as a data source from the Governor-General's office. In order to classify the data, the International Classification for Health Accounts (ICHA) method was used, in which data set was adjusted for the province. Results During the study, the governmental and non-governmental fund shares of the health sector in Kerman were 27.22% and 72.78% respectively. The main portion of financial sources (59.41) was related to private household funds, of which the Out-of-Pocket (OOP) payment mounted to 92.35%. Overall, 54.86% of all financial sources were covered by OOP. The greatest portion of expenditure of Total Healthcare Expenditures (THEs) (65.19%) was related to curative services. Conclusion The major portion of healthcare expenditures was related to the OOP payment which is compatible with the national average rate in Iran. However, health expenditure per capita, was two and a half times higher than the national average. By performing the Family Physician Program (FPP) and emphasizing Social Determinant of Health (SDH) approach in the Iranian health system, the portion of OOP payment and curative expenditure are expected to be controlled in the medium term. It is suggested that PHA should be examined annually in a more comprehensive manner to monitor initiatives and reforms in healthcare sector.